2013
DOI: 10.1038/embor.2013.109
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A kinase and its substrate TACC3 are required for central spindle assembly

Abstract: Cell division entails a marked reorganization of the microtubule network to form the spindle, a molecular machine that ensures accurate chromosome segregation to the daughter cells. Spindle organization is highly dynamic throughout mitosis and requires the activity of several kinases and complex regulatory mechanisms. Aurora A (AurA) kinase is essential for the assembly of the metaphase bipolar spindle and, thus, it has been difficult to address its function during the last phases of mitosis. Here, we examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
64
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 21 publications
6
64
0
1
Order By: Relevance
“…Our findings demonstrate that loss of TACC3, which is a centrosomal and cancer-associated adaptor protein (Kinoshita et al, 2005;Lioutas and Vernos, 2013;Yao et al, 2007), results in a centrosome-mediated cellular response that leads to G1 arrest and cell death. These results can be linked to earlier studies showing that centrosome defects interfere with cellular signaling pathways, which in turn trigger a stress response (Srsen et al, 2006;Mikule et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…Our findings demonstrate that loss of TACC3, which is a centrosomal and cancer-associated adaptor protein (Kinoshita et al, 2005;Lioutas and Vernos, 2013;Yao et al, 2007), results in a centrosome-mediated cellular response that leads to G1 arrest and cell death. These results can be linked to earlier studies showing that centrosome defects interfere with cellular signaling pathways, which in turn trigger a stress response (Srsen et al, 2006;Mikule et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…AURKA is a centrosome-and spindle-associated mitotic kinase with well-defined functions during early mitotic phases, including regulation of centrosome maturation and separation, mitotic entry and bipolar spindle assembly (Barr and Gergely, 2007;Nikonova et al, 2013). Recent studies have also revealed important roles in central spindle assembly in late mitotic stages and during interphase (Lioutas and Vernos, 2013;Nikonova et al, 2013;Reboutier et al, 2013). The expression of AURKA is upregulated in G2 and its activity is increased through interactions with protein activators and by kinase autophosphorylation primarily to facilitate mitotic entry (Bayliss et al, 2003;.…”
Section: Discussionmentioning
confidence: 99%
“…In human cells, TACC3 has been shown to be associated with the organization of the mitotic spindle poles (32). Subsequent studies revealed that TACC3 depletion induced chromosomal misalignment, reduced spindle stability, and triggered apoptosis in cells (33)(34)(35). However, the mechanism by which TACC3 regulates microtubule functions at the microtubule-organizing center (MTOC) has not been described.…”
mentioning
confidence: 98%